Poverty and inequality: Greece and Mediterranean Europe in comparative perspective - Teresa Munzi; Timothy Smeeding (Luxembourg Income Study (LIS), 2005)
Social vulnerability due to insufficient income and earnings may come from many sources, both demographic and economic, in a globalizing world. This paper examines the problems of population aging, low wages, growing inequality, and insufficient social spending. Vulnerable groups such as children and the aged are considered. The paper will look at the United States, Canada, and Europe using the LIS (Luxembourg Income Study) database, and especially with a focus on Greece whose data has recently been added to LIS. It will assess the net effects of existing policies and particularly the United Kingdom's program to reduce child poverty. While best practices may be identified, each nation must create its own set of mutually supportive policies which provide protection against global economic forces while at the same time encouraging self effort and efficient behavior. Still, policy can make a difference in outcomes as shown by the recent British success in fighting child poverty.
Keywords: 330; Armut; Einkommensverteilung; Kinder; Alte Menschen; Armutsbekämpfung; Vergleich; Disparitätsmaß; Griechenland; Europa; USA; Kanada